2018
DOI: 10.22159/ajpcr.2018.v11i1.22558
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and in Vitro Antioxidant Activity of Whole Plant Extracts of Sesuvium Portulacastrum L

Abstract: Objectives: The objectives of this study are to screen the phytochemicals, estimate the content of phenolic and flavonoid compounds, and determine the antioxidant capacity of the Sesuvium portulacastrum L. (S. portulacastrum). Methods:The crude bioactives were extracted from the dried powder of S. portulacastrum in an orbital shaker using ethanol, methanol, acetone, hexane, and diethyl ether solvents. Rotaevaporator was used to concentrate the extracts. Total phenolic and flavonoid content was estimated spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Nayak et al (2018) reported presence of saponins, terpenoids, tannins, alkaloids and steroids in the methanol leaf extracts of Suaeda maritima, besides their presence in other mangroves such as Xylocarpus granatum, Avicennia marina, Salvador apersica and Avicennia officinalis (Mulla and Chavan 2016). Similar to present study, ethanolic extract of Sesuviumportula castrum possesses phytochemicals like alkaloids, carbohydrates, cardiac glycosides, flavonoids, phenols, saponins, sterols, terpenoids, quinones, diterpenes, and resins contributed to its therapeutic value (Chintalapani et al 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Nayak et al (2018) reported presence of saponins, terpenoids, tannins, alkaloids and steroids in the methanol leaf extracts of Suaeda maritima, besides their presence in other mangroves such as Xylocarpus granatum, Avicennia marina, Salvador apersica and Avicennia officinalis (Mulla and Chavan 2016). Similar to present study, ethanolic extract of Sesuviumportula castrum possesses phytochemicals like alkaloids, carbohydrates, cardiac glycosides, flavonoids, phenols, saponins, sterols, terpenoids, quinones, diterpenes, and resins contributed to its therapeutic value (Chintalapani et al 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Nayak et al (2018) reported presence of saponins, terpenoids, tannins, alkaloids and steroids in the methanol leaf extracts of Suaeda maritima, besides their presence in other mangroves such as Xylocarpus granatum, Avicennia marina, Salvador apersica and Avicennia o cinalis (Mulla and Chavan 2016). Similar to present study, ethanolic extract of Sesuviumportula castrum possesses phytochemicals like alkaloids, carbohydrates, cardiac glycosides, avonoids, phenols, saponins, sterols, terpenoids, quinones, diterpenes, and resins contributed to its therapeutic value (Chintalapani et al 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Allow the mixture to stand for a minute. Formation of reddish-brown color in chloroform layer confirmed the presence of phytosterol [36,37].…”
Section: Salkowski Reactionmentioning
confidence: 99%
“…Folin-Ciocalteu reagent (FCR) assay was performed for the evaluation of TPC in the isolated plant extract [37,[44][45][46]. Take 150 µl of the extract and mixed in 240 µl of water and 150 µl of 0.25 N FCR.…”
Section: Determination Of Total Phenolic Content (Tpc)mentioning
confidence: 99%